Respiratory effects of surgery and pulmonary function testing in the preoperative evaluation - Chetta, A.; Tzani, P.; Marangio, et al., E. (Acta Biomedica Atenei Parmensis, 2006)
Advanced age, smoking habit, obesity or malnutrition, the coexistence of hypercapnia, bronchospasm or bronchial hypersecretion, the lack of pre-operative preparation and/or a prolonged duration of anaesthesia can negatively influence respiratory function in patients undergoing abdominal or thoracic surgery. Spirometric testing of pulmonary function is recommended in patients with a history of tobacco use or dyspnoea who are considered for cardiac or upper abdominal surgery and for all patients who are candidated for lung resection. Spirometry can provide cut-off values of acceptable risk in patients that are candidated for abdominal and thoracic surgery. At-risk patients having resective lung surgery should undergo a split lung function study with quantitative lung scanning or computed tomography in order to estimate the function of residual parenchyma after surgery. In patients with borderline estimated values, a cardiopulmonary exercise test is useful to further stratify surgical risk.